IMPROVING THE DEVELOPMENT OF MANAGERIAL COMPETENCIES OF GENERAL PRACTITIONERS IN POSTGRADUATE MEDICAL EDUCATION BASED ON A COMPETENCY-BASED APPROACH (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The article addresses current issues related to improving the development of managerial competencies among general practitioners in the context of modernization of postgraduate medical education. The necessity of implementing a competency-oriented educational model aimed at enhancing managerial thinking, decision-making skills, effective communication, and leadership within primary health care is substantiated. Existing educational approaches are analyzed, and their limitations in forming managerial competencies are identified. An optimized training model integrating clinical and managerial components and focused on practice-oriented outcomes is proposed. The results demonstrate the effectiveness and relevance of the competency-based approach in improving the quality of postgraduate medical education.
Keywords: General practitioner, managerial competencies, competency-based approach, postgraduate medical education, professional development.